UTILIZATION OF ONLINE QUEUE SYSTEM TECHNOLOGY TO IMPROVE PUBLIC SERVICE MANAGEMENT EFFICIENCY AT CLASS I IMMIGRATION OFFICE TPI SURABAYA - Faqim Adinul Falah; Fedianty Augustinah; Sapto Pramono; Widyawati Widyawati (DIA: Jurnal Administrasi Publik, 2025)
This research focuses on the utilization of Online Queue Systems to enhance the efficiency of public service management at the Immigration Office Class I TPI Surabaya. The implementation of this system is expected to address various issues related to conventional queues, such as long waiting times and customer discomfort. However, there are several aspects that still need to be examined, considering that the success of a public service system highly depends on effective queue management, procedure quality, and the readiness of personnel and supporting policies. The aim of this research is to analyze the impact of the Online Queue System on service quality and efficiency, identify existing challenges, and provide recommendations for system optimization. The research method used in this study is qualitative, with data collection conducted through direct observation, interviews, and document analysis related to the queue system at the immigration office. The findings show that the implementation of the Online Queue System has improved the efficiency and quality of public services, with public satisfaction reaching around 70%. Nonetheless, there is a need for further improvement in several aspects, such as queue management, information transparency, and waiting time. Additionally, technical readiness and supporting policies remain critical concerns, as there is still room to enhance personnel capacity and optimize policies to make the system more effective. The conclusion of this research emphasizes that while the Online Queue System has had a positive impact, several aspects still require attention and improvement to achieve higher efficiency. This research recommends several strategic steps, including increasing system capacity to handle surges in applicants, developing policies to support system operations, providing technical training for personnel, and conducting wider outreach to the public.